Faktor-Faktor Yang Mempengaruhi Keterampilan Motorik Dalam Pembelajaran - Bahridah, Puspita; Neviyarni, Neviyarni (JPT : Jurnal Pendidikan Tematik, 2021)
This article discusses learning motor skills using references from relevant studies, learning motor skills is a process of changing motion resulting from experience to achieve a quality goal of motion consisting of gross motor and fine motor development. There are three factors that influence learning motor skills, namely: (1) feedback, (2) distribution of practice, (3) stress and fatigue (stress and fatigue). Learning motor skills has several characteristics, namely: (1) response sequences, (2) perceptual motor coordination, (3) response settings (organization response), (4) feedback